Pre-Service Teachers’ Conceptual Understanding and Retention When Taught Osmosis Using Group Discussions - Kibirige, Israel (Journal of Innovative Science Education, 2023)
The effect of Group Discussions (GD) on pre-service teachers taught Osmosis was investigated using a quasi-experimental design with pre-and post-tests. Ninety-four pre-service teachers (N=47) for the Experimental Group (EG) taught using GD, and (N=47) for the Control Group (CG) were taught using the Traditional Approach (TA). Results from post-tests show EG performed better than CG, as indicated by Analysis of Covariance (ANCOVA), p < .05, suggesting that GD improved conceptual understanding. A Mann-Whitney U-test shows no significant differences in performance between males and females in EG, implying GD favoured both genders. In addition, EG retention was higher than CG when tested after an extended period. Thus, the results show that GD improves pre-service teachers’ conceptual understanding and retention. The implication for educators is that the use of GD in teaching biology improves pre-service teachers’ conceptual understanding of Osmosis, and these results have far-reaching implications in teacher education.